ANALISIS PENILAIAN SIKAP PEMBELAJARAN JARAK JAUH (PJJ) DI SD XAVERIUS 1 PALEMBANG - Septia Dwi Agusti (Jurnal PGSD Musi, 2021)
The Covid-19 pandemic has an impact on all human life including education, to reduce the impact of the pandemic, namely by reducing crowds and maintaining distance. The purpose of this study was to find out and describe how attitude assessment was in accordance with K13 during this pandemic at Xaverius 1 Elementary School Palembang. This research is a descriptive qualitative research. Data collection techniques were carried out by observation, interviews, and questionnaires. From the research, it was found that attitude assessment still exists online by continuing to use the K13 attitude assessment guide but slightly different aspects, methods, and instruments to adjust to the pandemic situation. Many difficulties are experienced in this attitude assessment, for example in selfassessment conducted through Google Forms it is difficult to guarantee the truth, in the assessment between friends they do not know each other, and in teacher observations it is difficult to know the real students because they can only judge fromcollection of assignments, attendance, and when PJJ via video call. Of course this PJJ has a positive impact as well, such as teachers and students being forced to use IT and students becoming more independent and creative.